A legal study on the sentences of syariah criminal offences in Malaysia: current practise and future change / Norashikin Jamil ... [et al.] - Jamil, Norashikin; Ibrahim, Monaliza; Hashim, Nur Hasyimah; Zainal, Nor Izariah (2010)
Recently, the issue regarding Syariah Criminal Law had been debated and discussed among academician, Non- Governmental Organization (NGOs) and public at large. The Criminal Offences and Sentences provided are not effectively applicable via the increasement of the Syariah Criminal cases and many more. This study explores on the sentences and offences provided in Syariah Criminal Law. Moreover, the purposes of the study are to discuss on the concept of sentencing, challenges and the reinforcement of the law itself. The results of these studies will be revealed, and the conclusion that there is a need for the improvement of Syariah Criminal Law will be discussed at the end of the chapter.